2006
DOI: 10.1111/j.1600-0668.2006.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the association between ventilation rates in classrooms and student performance

Abstract: Poor conditions leading to substandard indoor air quality (IAQ) in classrooms have been frequently cited in the literature over the past two decades. However, there is limited data linking poor IAQ in the classrooms to student performance. Whereas, it is assumed that poor IAQ results in reduced attendance and learning potential, and subsequent poor student performance, validating this hypothesis presents a challenge in today's school environment. This study explores the association between student performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
102
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(116 citation statements)
references
References 4 publications
6
102
1
4
Order By: Relevance
“…Due to the wrong choice of ventilation system and poor overall design, schools have generally very poor indoor climate [3]. Similar findings were obtained from investigations in buildings with different purposes which were poorly ventilated, such as offices, call centers etc.…”
Section: Introductionsupporting
confidence: 73%
“…Due to the wrong choice of ventilation system and poor overall design, schools have generally very poor indoor climate [3]. Similar findings were obtained from investigations in buildings with different purposes which were poorly ventilated, such as offices, call centers etc.…”
Section: Introductionsupporting
confidence: 73%
“…Failure to prevent or respond promptly to indoor air quality (IAQ) problems can increase short-and long-term health outcomes (Norbäck et al, 2000;Simoni et al, 2006;Tillet, 2010;Simoni et al, 2010), impact both teacher and student's attendance, comfort and performance (Gilliland et al, 2001;Shaughnessy et al, 2006;Mohai et al, 2011), and accelerate the deterioration of school buildings and equipments (Lohbeck, 2008). Among the indoor air pollutants, there is an increasing interest in the measurement of particulate matter concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…School absenteeism is one of the main problems in public and private school. Most of the incidence for total absent episodes and percent of missed days, including those because of upper respiratory infections [6,7]. Regards to Malaysia climate, these compilations has originate immensely among children and preschooler [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Asthma reported to be the number one cause for student absenteeism due to chronic conditions and was the leading cause of hospitalization for children [6]. Epidemiological data indicated that 7.4% of school-age children report having asthma symptoms annually, and 2.8 million children between 5 and 14 years of age had a diagnosis of asthma [11].…”
Section: Introductionmentioning
confidence: 99%